Ruminal utilization of nitrogen derived from 15N-labeled faba beans in vitro - Räisänen, S.E.; Sigurðardóttir, Þ.H.; Halmemies-Beauchet-Filleau, A.; Pitkänen, O.; Honkanen, A.; Kokkonen, T.; Stoddard, F.L.; Simojoki, A.; Salhlstedt, Elina; Rinne-Garmston, Katja; Vanhatalo, A. (Elsevier, 2025)
The aim of this short-term in vitro study was to characterize and evaluate ruminal utilization of N fractions of faba bean protein. Faba bean seeds were grown using a 15N-enriched N-fertilizer and fractionated into insoluble N (INSN), NDIN, NPN, and soluble protein N (SPN). Unfractionated ground 15N-labeled faba bean seeds (FB) were used as a reference treatment. Batches of the N fractions and FB were incubated for 10 h in an automatic Gas Endeavor in vitro batch-culture system with 3 replicated incubations. Purified mono-, di-, and polysaccharides were used as an energy source. The ratio of buffer to rumen fluid, obtained from 2 rumen-cannulated cows, was 2:1. The incubation medium was sampled at 0, 0.5, 1, 2, 5, and 10 h after the start of incubation. Subsequently, the incubation medium was separated into low- (i.e., feed and protozoa) and high-speed centrifugate (i.e., bacterial) N pools and ammonia-N pool, and 15N enrichment of each pool was measured. Due to low gas and VFA production, data for NPN fraction were not included in the dataset. The faba bean seeds contained (% of CP) 54% SPN, 18% NPN, 17% NDIN, 10% true protein soluble in neutral detergent, and 2% ADIN. At the end of incubation, the recovery of 15N in the ammonia-N pool was greatest for FB (12%) and SPN (7%) compared with the INSN (2%) and NDIN (0.06%) fractions. The recovery of 15N in the bacterial-N pool was numerically greatest for the FB treatment (15%), followed by INSN and SPN (6%), and was lowest for the NDIN treatment (0.75%). In line with our hypothesis, ruminal metabolism of N differed between the N fractions of faba bean being greatest for the SPN fraction, and minimal for the NDIN. Future studies should confirm the findings from this short-term in vitro batch-culture study, and further investigate the degradation and ruminal utilization of faba bean soluble N and its contribution to MP supply in dairy cows fed diets with varying protein and energy contents.
Keywords: ruminal utilization; faba beans; proteins